Key capabilities required for podiatry graduates: A Delphi consensus study - Shannon E. Munteanu; Matthew Cotchett; Matthew J. Oates; Nicoletta Frescos; Vivienne Chuter; Mike Frecklington; Marie T. Butler; Nick W. Haley; Hylton B. Menz (Journal of Foot and Ankle Research)
Abstract Introduction Work‐readiness is linked to health professional graduates' job performance, satisfaction, engagement and retention. However, there is currently no podiatry‐specific graduate employer work‐readiness survey tool that has been developed with employers of graduate podiatrists. The aim of this study was to conduct a modified Delphi survey to achieve consensus among employers of podiatry graduates on the key capabilities required for podiatry graduates. Methods A Delphi method of consensus development was used, comprising three online survey rounds. Purposive sampling was used to recruit individuals with extensive experience and knowledge in mentoring and managing graduate podiatrists in Australia or New Zealand. In Round 1, participants were asked to rate agreement/disagreement with 71 items across seven domains relating to capabilities required of podiatry graduates that were extracted from a literature search and steering committee input. Participants were also asked to contribute further ideas in relation to these items, which were incorporated as new items (n = 7) in Round 2. In Rounds 2 and 3, participants re‐appraised their ratings in view of the group consensus. Consensus was defined as ≥75% agreement. In Round 3, participants were also asked to rate the importance of each item as either ‘essential’ or ‘optional’. Results Twenty‐five participants (mean [SD] of 14.9 [5.7] years of experience in managing podiatry graduates in clinical practice in Australia or New Zealand) completed Round 1, 24 in Round 2, and 23 in Round 3. Of the 78 items presented to our expert panel, 61 (78.2%) achieved consensus and were accepted, and 17 (21.8%) were excluded. Of the 61 items that achieved consensus, thirty‐nine (63.9%) were rated as ‘essential’ by 75% of more respondents. Conclusion Consensus among employers of podiatry graduates was established on the key capabilities required for podiatry graduates. Sixty‐one items were identified across seven domains, and of these, 39 items were rated as ‘essential’. The findings of this study have the potential to inform the creation of a podiatry‐specific graduate employer work‐readiness tool to provide feedback to podiatry education program providers and new graduates in the workplace.